The history of cryptography - Meyer, Susan, 1986- (Cryptography: code making and code breaking., 2017)
"Cryptography stretches all the way back into ancient times and has been evolving ever since. From Julius Caesar to the modern cryptography of computers, [the author relates] ... stories and examples of how some of the greatest minds of history have figured out how to make and break codes"--Provided by publisher.